2012
DOI: 10.1103/physrevlett.109.195001
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Dissipation at Kinetic Scales in Collisionless Plasma Turbulence

Abstract: High resolution kinetic simulations of collisionless plasma driven by shear show the development of turbulence characterized by dynamic coherent sheetlike current density structures spanning a range of scales down to electron scales. We present evidence that these structures are sites for heating and dissipation, and that stronger current structures signify higher dissipation rates. Evidently, kinetic scale plasma, like magnetohydrodynamics, becomes intermittent due to current sheet formation, leading to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
163
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(189 citation statements)
references
References 33 publications
26
163
0
Order By: Relevance
“…Various studies based on numerical simulations [24,25,27,[47][48][49][50] and solar wind data [23,[51][52][53][54] support the idea that enhanced kinetic activity, such as temperature anisotropy, heating, particle acceleration, and departures from Maxwellian velocity distributions in general, all of which commonly observed in astrophysical and laboratory plasmas, are strongly inhomogeneous. These effects are associated typically with coherent structures such as magnetic structures.…”
Section: A Energy Conversion Related To Coherent Structuresmentioning
confidence: 99%
“…Various studies based on numerical simulations [24,25,27,[47][48][49][50] and solar wind data [23,[51][52][53][54] support the idea that enhanced kinetic activity, such as temperature anisotropy, heating, particle acceleration, and departures from Maxwellian velocity distributions in general, all of which commonly observed in astrophysical and laboratory plasmas, are strongly inhomogeneous. These effects are associated typically with coherent structures such as magnetic structures.…”
Section: A Energy Conversion Related To Coherent Structuresmentioning
confidence: 99%
“…(Here the proton/electron mass ratio is 100.) Using the same simulation, Wan et al [131] analysed the work done by the electromagnetic field on the plasma. Quantitatively this is given by J · E, where the electric current density is J and the electric field is E. Somewhere buried in this quantity is the work done in producing random motions, i.e.…”
Section: Plasma Intermittency At Kinetic Scalesmentioning
confidence: 99%
“…Still another variation computes the work using only the current associated with electrons. Wan et al [131] examined all of these, and found in each case that the corresponding work done on the particles is concentrated in sheet-like regions, again spanning a range of scales from ≈ d i to below the electron inertial scales. It was found for example that 70% of the work done on the particles occurs in regions of strong current that occupy less than 7% of the total plasma volume.…”
Section: Plasma Intermittency At Kinetic Scalesmentioning
confidence: 99%
“…Boldyrev [14] has introduced the concept of dynamic alignment, in which the velocity and magnetic fluctuations in the plane perpendicular to the mean field become increasingly aligned at smaller scales, producing sheet-like structures rather than filaments. Such structures can dissipate energy intermittently [15]. Some resistive MHD simulations have shown strong current sheets that occupy 1% of the simulation volume but account for 25% of the resistive dissipation [16].…”
Section: Introductionmentioning
confidence: 99%